2020
DOI: 10.1021/acs.estlett.0c00557
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Isotope Effects in Electrophilic Aromatic Halogenation of Dimethenamid in Chlor(am)inated Water Demonstrate Unique Aspects of Iodination

Abstract: Electrophilic aromatic substitution reactions can initiate halogenated disinfection byproduct (DBP) formation. The rate-controlling step (RCS) of electrophilic aromatic halogenation is commonly assumed to be halogen addition (vs proton removal), although this assumption has not been previously assessed under water disinfection conditions. Herein, the herbicide dimethenamid (DM) was used as a model aromatic compound to examine the RCS of halogenation in water treated with free chlorine (chlorination), free chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 46 publications
(133 reference statements)
2
12
0
Order By: Relevance
“…Accordingly, we concluded that H 2 OI + could participate in the iodination mechanism before rate-controlling proton removal, which agrees with the experimental results in a previous study. 25 Comparing the most favorable route for the Tyr-Gly and HOI reaction (R B in Figure 1) with the Tyr-Gly and H 2 OI + reaction (R E in Figure 3), the energy barrier of the H 2 OI + reaction route R E is 31.4 kcal mol −1 lower than that of the HOI route R B . Furthermore, the calculated rate constant of route R E is 6.15 × 10 7 M −1 s −1 , and its reaction rate is 1.93 × 10 −3 M s −1 , which is 23 orders of magnitude higher than that of the HOI reaction (route R B ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Accordingly, we concluded that H 2 OI + could participate in the iodination mechanism before rate-controlling proton removal, which agrees with the experimental results in a previous study. 25 Comparing the most favorable route for the Tyr-Gly and HOI reaction (R B in Figure 1) with the Tyr-Gly and H 2 OI + reaction (R E in Figure 3), the energy barrier of the H 2 OI + reaction route R E is 31.4 kcal mol −1 lower than that of the HOI route R B . Furthermore, the calculated rate constant of route R E is 6.15 × 10 7 M −1 s −1 , and its reaction rate is 1.93 × 10 −3 M s −1 , which is 23 orders of magnitude higher than that of the HOI reaction (route R B ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In light of previous studies reporting that H 2 O could be involved in the iodination processes, 25,32 route R E in Figure 3 examines the involvement of the solvent water molecule acting as a weak Brønsted base for the leaving proton in the H 2 OI + and Tyr-Gly reaction. This reaction is a stepwise mechanism with fast formation of complex (Com1) [H 2 OI + •••Tyr-Gly] followed by a rate-controlling deprotonation reaction that resulted in the formation of I-Tyr-Gly.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations